Analisis Lama Mencari Kerja bagi Tamatan Universitas Riau - Yani, Ahmad; Hamidi, Wahyu; Setiawan, Deny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the cause of working for the long seek graduate of the University of Riau. Data were drawn from this study obtained at Riau University Academic Section from 2008 to 2012. Research uses descriptive research method derived from the questionnaire given to the students graduate of the University of Riau. From the data obtained and questionnaires that the desire of a person with a high wage to be able to meet the needs of the higher life. Generally, a person willing to spend a long time to have a job with great pay. And also with the job information available in print and online can give someone the opportunity to work even greater. So also with the presence of sex differences required by a company, because sometimes different genders, different types of jobs is also suitable for obtainment. Keywords: Wages, Information, Sex.